2011
DOI: 10.1007/s12223-011-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of external factors on bacteriophages—review

Abstract: The ability of bacteriophages to survive under unfavorable conditions is highly diversified. We summarize the influence of different external physical and chemical factors, such as temperature, acidity, and ions, on phage persistence. The relationships between a phage’s morphology and its survival abilities suggested by some authors are also discussed. A better understanding of the complex problem of phage sensitivity to external factors may be useful not only for those interested in pharmaceutical and agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
441
1
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(476 citation statements)
references
References 67 publications
18
441
1
16
Order By: Relevance
“…Our results in agreement with Jonczy et al (2011), which they approved that some phage can be stored for a long period in neutral pH (6)(7)(8). This experiments testing the pH tolerance of the bacteriophages confirmed that the pH was very important for the infectivity of the phages.…”
Section: Of Bacteriophage Against Mrsasupporting
confidence: 92%
“…Our results in agreement with Jonczy et al (2011), which they approved that some phage can be stored for a long period in neutral pH (6)(7)(8). This experiments testing the pH tolerance of the bacteriophages confirmed that the pH was very important for the infectivity of the phages.…”
Section: Of Bacteriophage Against Mrsasupporting
confidence: 92%
“…If contamination is discovered, a phage aliquot from a previous round can then be used to continue the process. Freezing and thawing the phages several times may be harmful to stability and so it is beneficial to perform many of the negative panning steps continuously 31 . Because the panning process does not utilize phage amplification steps after each round of positive panning 32 the process is less likely to isolate empty or incomplete phage sequences.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Temperature determines the occurrence and viability of the phages in different environments. In terms of pH, some phages persist well in acidic environments (19), but this is not the case for Cdt phages, which lose their infectivity when stored for 1 day at pH 3. In contrast, Cdt phages retain their infectivity better at pH 7 and 9, which is in line with reports of phage (17).…”
Section: Discussionmentioning
confidence: 98%